Facet Engineering to Regulate Surface States of Topological Crystalline Insulator Bismuth Rhombic Dodecahedrons for Highly Energy Efficient Electrochemical CO2 Reduction. Issue 31 (26th June 2021) - Xie, Huan; Zhang, Tan; Xie, Ruikuan; Hou, Zhufeng; Ji, Xuecong; Pang, Yongyu; Chen, Shaoqing; Titirici, Maria‐Magdalena; Weng, Hongming; Chai, Guoliang
Abstract: Bismuth (Bi) is a topological crystalline insulator (TCI), which has gapless topological surface states (TSSs) protected by a specific crystalline symmetry that strongly depends on the facet. Bi is also a promising electrochemical CO2 reduction reaction (ECO2 RR) electrocatalyst for formate production. In this study, single‐crystalline Bi rhombic dodecahedrons (RDs) exposed with (104) and (110) facets are developed. The Bi RDs demonstrate a very low overpotential and high selectivity for formate production (Faradic efficiency >92.2%) in a wide partial current density range from 9.8 to 290.1 mA cm −2, leading to a remarkably high full‐cell energy efficiency (69.5%) for ECO2 RR. The significantly reduced overpotential is caused by the enhanced *OCHO adsorption on the Bi RDs. The high selectivity of formate can be ascribed to the TSSs and the trivial surface states opening small gaps in the bulk gap on Bi RDs, which strengthens and stabilizes the preferentially adsorbed *OCHO and mitigates the competing adsorption of *H during ECO2 RR. This study describes a promising application of Bi RDs for high‐rate formate production and high‐efficiency energy storage of intermittent renewable electricity. Optimizing the geometry of TCIs is also proposed as an effective strategy to tune the TSSs of topological catalysts. Abstract : The topological surface states and the trivial surface states opening small gaps in the bulk gap of Bi rhombic dodecahedrons facilitate highly selective formate production in a wide current density range, leading to a high full‐cell energy efficiency (maximum value of 69.5%) for electrochemical CO2 reduction reaction. This electrocatalyst can potentially be used for intermittent energy storage.